(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The economic security of banks plays a pivotal role in the broader financial stability of any economy. This article assesses the financial sustainability and stability of banks as key indicators of their economic security. Through an analysis of various risk factors, regulatory frameworks, and financial indicators, this research examines how banks maintain security in an increasingly volatile economic environment. The study evaluates the factors influencing the financial security of banks and offers a comparative assessment across different banking systems to propose recommendations for enhanced financial resilience.